Factors Influencing Physical Activity and Healthy Lifestyle on Students' Physical Fitness - Reni Silviah (Siber International Journal of Sport Education, 2026)
Factors that influence physical activity and healthy lifestyle on students' physical fitness is a scientific article with the aim of analyzing whether physical activity and healthy lifestyle affect physical fitness. The method with a qualitative phenomenological approach, the phenomenological approach emphasizes the description of the subject's life experience from the participant's own perspective (phenomenology as a social research method). The results of this article are: 1) Physical activity affects physical fitness, 2) Healthy lifestyle affects physical fitness. Apart from these 2 exogenous variables that influence the endogenous variables of physical fitness, there are still many other factors including discipline, sports motivation, mental health.